BBGKY hierarchy and its evolution operator for one class of integrable systems - Skrypnik, W.I. (Український математичний журнал, 1995)
We define the abstract BBGKY hierarchy and its formal evolution operator. The existence of the latter is established in a special Banach space for a system of charged particles with Chern-Simons interaction regularized for small and large distances. An analog of the high-temperature expansion of equilibrium statistical mechanics is applied. Визначені абстрактна ієрархія ББГКІ та її формальний еволюційний оператор. Встановлено існування цього оператора в спеціальному банаховому просторі для інтегровної системи заряджених частинок із взаємодією Черна-Саймонса, яка регуляризована на малих та великих відстанях. При цьому використовується аналог високотемпературного кластерної о розкладу рівноважної статистичної механіки.